Short communication: Characterization of the milk protein expression profiles in dairy buffaloes with and without subclinical mastitis - Tanamati, Fernanda [UNESP]; Taylor, Jeremy F.; Behura, Susanta K.; Santos, Daniel J.A.; Stafuzza, Nedenia B.; Andrade, Willian B.F. [UNESP]; Gasparino, Eliane; Tonhati, Humberto [UNESP] (American Dairy Science Association, 2020)
The aim of this study was to characterize the proteins present in milk whey from buffaloes with and without subclinical mastitis using a proteomic approach to identify differentially expressed proteins as potential biomarkers for this disease. Whey from Murrah buffaloes with subclinical mastitis was compared with whey from healthy animals using liquid chromatography–tandem mass spectrometry. The annotated protein databases for Bubalus bubalis and Bos taurus were used in the analysis, and the gene annotations from the buffalo and bovine reference assemblies were also used. After integrating gene annotations from both buffaloes and bovines, a total of 1,033 proteins were identified, of which 156 were differentially expressed. Eighteen biological processes were annotated with Gene Ontology. Cathelicidin-3 was identified as a potential biomarker for subclinical mastitis. These results are important to the characterization of mastitis in the buffalo mammary gland and may aid in the development of tools for early diagnosis.
Keywords: Bubalus bubalis; cathelicidin-3; milk whey protein; proteomics